2017
DOI: 10.3389/fphar.2017.00783
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside-Rb1-Mediated Anti-angiogenesis via Regulating PEDF and miR-33a through the Activation of PPAR-γ Pathway

Abstract: Angiogenesis is the formation of new blood vessels from the existing vasculature, which is involved in multiple biological processes, including atherosclerosis, ischemic heart disease, and cancer. Ginsenoside-Rb1 (Rb1), the most abundant ginsenoside isolated form Panax ginseng, has been identified as a promising anti-angiogenic agent via the up-regulation of PEDF. However, the underlying molecular mechanisms still unknown. In the present study, human umbilical vein endothelial cells (HUVECs) were selected to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…Studies have implied that ginsenosides function through nuclear receptors . Our previous study also suggests that ginsenoside Rb1 activates PPAR‐γ in HUVECs . Interestingly, new metabolites of Rb1 by microbial transformation have been reported to activate the Wnt/β‐catenin pathway, which mediates the induction of osteogenic differentiation in MC3T3‐E1 cells .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Studies have implied that ginsenosides function through nuclear receptors . Our previous study also suggests that ginsenoside Rb1 activates PPAR‐γ in HUVECs . Interestingly, new metabolites of Rb1 by microbial transformation have been reported to activate the Wnt/β‐catenin pathway, which mediates the induction of osteogenic differentiation in MC3T3‐E1 cells .…”
Section: Discussionmentioning
confidence: 79%
“…In view of the demonstration that Rb1 acts as a PPAR‐γ agonist in human umbilical vein endothelial cells (HUVECs) by our previous study, we hypothesized that ginsenoside Rb1 may protect VC through the PPAR‐γ/β‐catenin axis. To test our hypothesis, we established a CKD rat model and a VSMC calcification model to mimic clinical CKD‐associated VC in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that activating PPAR-γ signaling pathway played pivotal role in PEDF's beneficial effects [25][26][27][28][29]. PPAR-γ knockdown could reduce PEDF expression [30]. The decrease of PEDF was significantly down-regulated and the increase of NF-κB and MMP-9 was down-regulated by systemically administration of PPAR-γ agonist [31].…”
Section: Discussionmentioning
confidence: 99%
“…All of the beneficial effects of PEDF on AGE-exposed podocytes were blocked by the treatment of GW9662, an inhibitor of PPAR-γ [32]. PEDF increment on human endothelial cells was blocked by the preincubation with GW9662, which resulted in the promotion of angiogenesis [30]. Moreover, it had been suggested that PEDF could interact with PPAR-γ for the regulation of angiogenesis and lipid metabolism in hepatocellular carcinoma [33], and it is necessary for protective roles of PEDF in OGD cardiomyocytes [34].…”
Section: Discussionmentioning
confidence: 99%
“…have a good inhibitory effect on microglia-mediated neuroinflammation, which could promote the expression of anti-inflammatory cytokines by activating PPAR-γ signaling pathways (Lu et al, 2017, Zhang et al, 2018a.…”
Section: Introductionmentioning
confidence: 99%